PENGARUH LITERASI KEUANGAN IBU RUMAH TANGGA TERHADAP PERILAKU PENGELOLAAN KEUANGAN KELUARGA DIMODERASI OLEH TINGKAT PENDIDIKAN DAN PEKERJAAN DI KALURAHAN NGARGOSARI - Kurniawati, Diana Dwi; Eko Astuti, Murwani (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to influence the financial literacy of housewives on family financial management behaviour with moderating variables of education and employment. Using primary data sources with quantitative research types, with research subjects of housewives in Ngargosari Village totalling 69 people. The sampling technique with non-probability sampling is purposive sampling, using a questionnaire or questionnaire. For data analysis techniques using SEM and Moderated Regression Analysis (MRA). With the results of the study, the financial literacy of housewives has a significant effect on family financial management behaviour in Ngargosari Village. financial literacy of housewives with a moderate of education level has a significant effect on family financial management behaviour in Ngargosari Village, Kulon Progo. Financial literacy of housewives with a moderate of employment level has no significant effect on family financial management behaviour in Ngargosari Village, Kulon Progo. Keywords: Financial Literacy, Financial Management Behaviour, Education, Employment.